2015
DOI: 10.1016/j.jnoncrysol.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soda-lime glasses using non-negative matrix factor deconvolution of Raman spectra

Abstract: Novel statistical analysis and machine learning algorithms are proposed for the deconvolution and interpretation of Raman spectra of silicate glasses in the Na 2 O-CaO-SiO 2 system. Raman spectra are acquired along diffusion profiles of three pairs of glasses centered around an average composition of 69.9 wt.% SiO 2 , 12.7 wt.% CaO, 16.8 wt.% Na 2 O. The shape changes of the Raman spectra across the compositional domain are analyzed using a combination of principal component analysis (PCA) and sparse non-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
(97 reference statements)
2
17
0
Order By: Relevance
“…[NbO6] octahedra have high Raman cross sections and the peak at 875 cm -1 is detectable at low (>0.10mol%) concentrations in SLS glasses [263,264] and is present in Figure 57, Figure 58 and Figure 59. Deconvolution of Nb2O5 spectra along with base SLS through the program FitYK shown in Figure 61, give a BO:NBO ratio of circa 64:36 indicating high polymerisation and non-significant changes to the polymerisation with the incorporation of 0.20mol% Nb2O5 and are consistent with other similar glasses [262]. Molybdate tetrahedra likewise present strong Raman cross sections, thus giving rise to a stronger signal relative to the corresponding network [265] demonstrated in Figure 57.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…[NbO6] octahedra have high Raman cross sections and the peak at 875 cm -1 is detectable at low (>0.10mol%) concentrations in SLS glasses [263,264] and is present in Figure 57, Figure 58 and Figure 59. Deconvolution of Nb2O5 spectra along with base SLS through the program FitYK shown in Figure 61, give a BO:NBO ratio of circa 64:36 indicating high polymerisation and non-significant changes to the polymerisation with the incorporation of 0.20mol% Nb2O5 and are consistent with other similar glasses [262]. Molybdate tetrahedra likewise present strong Raman cross sections, thus giving rise to a stronger signal relative to the corresponding network [265] demonstrated in Figure 57.…”
supporting
confidence: 69%
“…Raman spectra of base and doped glasses are shown in Figure 57. Each trace is composed of five main peaks, consistent with other float and soda lime silica systems [261,262]. Samples doped with Nb2O5 and MoO3 have an additional peak highlighted by…”
Section: Raman Spectroscopysupporting
confidence: 56%
“…2). 37 NMF has been used to deconvolute spectra in the field of Raman spectroscopy, and a powerful aspect of this analysis algorithm is that a set of partial Raman spectrum (PRS) as well as the amplitude of each PRS during the spectral evolution can be obtained without any assumption concerning the spectral shapes. The number of PRS used for the deconvolution is the only predetermined parameter.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure consistently yielded clear, bubble‐free, and visually homogeneous glass plates (Figure 1). The chemical homogeneity of samples synthesized by this procedure was assessed by electron microprobe analysis (EMPA) in a prior study on samples of similar volume and compositions, which showed to be homogeneous with standard deviations below 0.02 wt% [14] . For the sake of simplicity, this paper will highlight results from a sample that is at the center of the composition range.…”
Section: Methodsmentioning
confidence: 99%